Identifikasi Kebutuhan Belajar Dan Manajemen Diri Pasien Gagal Ginjal Terminal Yang Menjalani Hemodialisis Di Rumah Sakit Tangerang - Chris Veronica Gultom, Eva; Natalia Watania, Lani; Pailak, Heman; Harapan Telaumbanua, Daniel; Arisman Laoli, Jevrianus; Rudiyatin, Lili; Taruk Lola, Gustianus (STIKES Suaka Insan, 2024)
The patient's learning needs include the need for information on health status which includes many things, namely medicines, skin care, and others. The existence of this need is in line with the patient's self-management in caring for the body through relationships with nurses and patients to emotional management. The purpose of the study was to identify the learning needs and self-management of terminal renal failure patients undergoing hemodialysis. The benefits that can be obtained from the results of the study can be used as a basis for intervening in the form of education and peer support programs for patients. The research was conducted using descriptive quantitative method with cross sectional approach. The sample in this study were 190 terminal renal failure patients undergoing hemodialysis at Siloam Lippo Village Tangerang Hospital Building A and Building B. The sampling technique used was total sampling. The sampling technique used was total sampling. The results showed the mean value of patient learning needs 205.85 ± 17.53, the mean value of self-management 96.21 ± 9.36.